1994
DOI: 10.1161/01.cir.90.6.2905
|View full text |Cite
|
Sign up to set email alerts
|

Relation of smoking with carotid artery wall thickness and stenosis in older adults. The Cardiovascular Health Study. The Cardiovascular Health Study (CHS) Collaborative Research Group.

Abstract: These findings extend previous reports of a positive relation between smoking and carotid artery disease to a population-based sample of older adults using several different indicators of atherosclerotic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(58 citation statements)
references
References 21 publications
2
52
1
2
Order By: Relevance
“…[11][12][13] Further, there is abundant evidence for a strong association between cigarette smoking and extracranial carotid artery morphologic changes. 14,15 These pathologic changes may represent a better marker for, and be more discriminating than, accelerated atherosclerosis as a measure of smoking-related arterial injury. The influence of the altered physical characteristics of peripheral vasculature associated with acute cigarette smoking on pulsatile arterial function has not been rigorously studied.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Further, there is abundant evidence for a strong association between cigarette smoking and extracranial carotid artery morphologic changes. 14,15 These pathologic changes may represent a better marker for, and be more discriminating than, accelerated atherosclerosis as a measure of smoking-related arterial injury. The influence of the altered physical characteristics of peripheral vasculature associated with acute cigarette smoking on pulsatile arterial function has not been rigorously studied.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] Some studies have failed to report a difference in C-IMT between former and current smokers, 6,12 which suggests that the effect of smoking on vascular walls is irreversible; yet, categorizations that do not take into account the extent and timing of smoking may yield misleading conclusions. For example, an individual with a 40-year history of cigarette smoking who stopped smoking 1 year ago is classified as a former smoker, but his/her C-IMT may well not differ from that of a current smoker.…”
mentioning
confidence: 99%
“…In addition, carotid artery atherosclerotic disease has been found with high prevalence in elderly patients with hypertension, hyperlipidemia, smoking, and DM. 13,14) The study of Adler, et al 8) was the first that showed a strong and significant association between the presence of MAC and carotid atherosclerosis. According to the results of their study, in the MAC group, MAC and age were the only independent predictors for carotid artery stenosis of ≥ 40%.…”
Section: Discussionmentioning
confidence: 99%